Morphine or Tramadol Administration by Epidural Route in Horses - Clinical Evaluation - Leite, Alline Morgana Silva; Bertonha, Cândice Mara; Valadão, Carlos Augusto Araújo [UNESP]; Cholfe, Bruno Fornitano; Takeda, Murilo (Universidade Federal do Rio Grande do Sul, 2024)
Background: Opioids are widely used in veterinary medicine, but their use is restricted in horses due to their potential adverse effects, such as reduced intestinal motility and excitation. Morphine and tramadol are opioids recommended for pain control in horses, and the absorption of these drugs by the epidural route is relatively slow due to low lipid solubility, resulting in longer duration of the analgesic effect and a reduction in undesirable effects. This study aimed to monitor the clinical and behavioral alterations in horses administered morphine or tramadol by the epidural route. Materials, Methods & Results: Eight horses (2 males and 6 females) with mean weight of 336.3 ± 33.4 kg and age of 5.5 ± 1.3 years were allocated to 3 groups in a cross-over design, in which tramadol (TG) [1 mg/kg], morphine (MG) [0.2 mg/ kg], and 0.9% NaCl (CG) were administered in a previously implanted epidural catheter. The clinical parameters heart rate (HR), respiratory rate (rR), rectal temperature (RT) were measured before treatment administration (MB), 5 (M5), 10 (M10), 20 (M20), 30 (M30), 40 (M40), 50 (M50), and 60 min (M60) after epidural injection. Intestinal motility scores, latency to defecate, and behavioral alterations were evaluated at MB, M10, M30, M60, 120 (M120), 240 (M240), 480 (M480), and 960 min (M960) after treatment administration. Parametric data were subjected to one-way analysis of variance with the Student-Newman-Keuls retest and non-parametric data to the Friedman or Kruskal-Wallis test followed by the Dunn's test, both with significance set at P ≤ 0.05. Rectal temperature increased considerably in the CG animals from MB (36.8°C) to M60 (37.4°C) and in the MG at M20 and M60 (37.4°C) in relation to MB (36.9°C). The values of HR, rR, and motility scores on the left side did not vary significantly between groups and moments. However, there was a 40% reduction in right-sided intestinal motility scores (upper and lower quadrants) in the MG. In addition, the total intestinal motility score (sum of the four quadrants), 30 min after treatment administration, remained reduced until M120, compared to MB. Concomitantly, 50% of the MG animals had increased latency to defecate, although this was not significant. Discussion: The maintenance of heart rate and respiratory rate parameters after administration of morphine [0.2 mg/kg] by the epidural route is related to the absence of sympathetic interference and the route of administration. Similarly, the study found no significant differences in the cardiorespiratory system after epidural administration of tramadol at a dose of 1 mg/kg. Generally, such alterations are associated with high doses, associations with other pharmacological classes, or exacerbated use of the opioid. The increase in body temperature in CG and MG is presumably associated with climatic conditions, as it was believed that opioids did not interfere with this parameter. The drop in right-sided and total intestinal motility scores in MG triggered an increase in latency to defecate, which may be associated with the blockade of opioid receptors in the myenteric nervous system, which promotes a reduction in cholinergic tone. There were no alterations in the motility score and latency to defecate after epidural administration of tramadol, as there were after oral or intravenous administration. The slight alterations and absence of variations in clinical parameters caused by the administration of morphine and tramadol by the epidural route in horses, respectively, reinforce the use of these drugs in pain control, given their analgesic potential, already proven in previous studies.
Keywords: analgesia; equine; motility; opioids; pain control